Potencial da semeadura direta na restauração florestal de pastagem abandonada no município de Piracaia, SP, Brasil1 - Aguirre, Andrea Garafulic [UNESP]; Lima, Juliana Toledo; Teixeira, Juliana; Gandolfi, Sergius (Instituto de Botânica, 2015)
The successful establishment of tree species in pastures may be related to the species used, germination conditions, and seed size. The aim of this study was to evaluate the effectiveness of treatments: pre-hydration and different kinds of seed coverage in eight native species with different seed sizes and verify if these species would be able to produce 1,666 individual ha-1 after one year. Five of the eight species tested had potential for large-scale use with the higher germination rate for the small seeds. The pre-hydration of the seeds was not efficient in increasing the germination and in the establishment of species, but coverage with straw and soil showed important results. The best result was obtained with the treatment of seed coverage with soil without hydration, with the establishment of 3,817 seedlings ha-1 after one year.

O sucesso do estabelecimento de espécies arbóreas em pastagens pode estar relacionado a espécie utilizada, condições de germinação e tamanho das sementes. O objetivo desse trabalho foi avaliar a eficiência dos tratamentos: pré‑hidratação e diferentes coberturas em oito espécies nativas com diferentes tamanhos de sementes e verificar se estas seriam capazes de produzir após um ano 1.666 indivíduos ha-1. Cinco espécies testadas apresentaram potencial para uso em grande escala, sendo que as sementes pequenas obtiveram a maior taxa de germinação. A pré-hidratação das sementes não se mostrou eficiente no aumento da germinação e estabelecimento das espécies, mas a cobertura por palha ou terra foi de grande importância. O melhor resultado obtido foi com o tratamento das sementes cobertas com terra e sem hidratação, com estabelecimento de 3.817 mudas ha-1 após um ano.
Potential of direct seeding in forest restoration of an abandoned pasture in the municipal area of Piracaia, São Paulo State, Brazil
Keywords: seed coating; seed pre-hydration; seed size; pré-hidratação de sementes; recobrimento de sementes; tamanho de sementes